(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The present paper provides some solutions of Einstein Maxwell field equations for SomeCharged Fluid Spheres by using a judicious choice of metric potential g11 and g44. The central andboundary conditions have been also discussed